Parental marital disruption, family type, and transfers to disabled elderly parents - Liliana E. Pezzin; Robert A. Pollak; Barbara Steinberg Schone (Institute for the Study of Labor (IZA), 2008)
This paper examines the family variables that affect intergenerational living arrangements and adult children's time and cash transfers to their unpartnered disabled elderly parents. The family variables we examine include parental marital status, parental marital history, whether the index child is a step child or a biological child of the parent, and whether the index child's siblings are step children or biological children of the parent. Using data from the Health and Retirement Studies - Asset and Health Dynamics Among the Oldest Old (HRS-AHEAD) surveys, we estimate the joint probabilities that an adult child provides time and/or cash transfers to a parent and analyze a five-level categorical variable capturing parentchild living arrangements. Parameter estimates suggest significant detrimental effects of parental divorce and step relationship on time transfers and on the probability of coresidence with the index child. The composition of the index child's sibling network also affects transfers and living arrangement choices of adult children. Our findings suggest that demographic changes are weakening the traditional role of the family as a support network. Because more recent cohorts of elderly persons have experienced substantially higher rates of divorce, remarriage, and step parenthood than the cohort considered in this study, our findings raise concerns about the future availability of family care.
urn:nbn:de:101:1-20081127557
Keywords: I10; 330; Intergenerational transfers; aging; long-term care; family; Alleinlebende; Alte Menschen; Privater Transfer; Familiensoziologie; Generationenbeziehungen; Pflegedienst; Sozialer Wandel; USA